OpenSHMEM and related technologies : OpenSHMEM in the era of extreme heterogeneity : 5th Workshop, OpenSHMEM 2018, Baltimore, MD, USA, August 21-23, 2018, Revised Selected Papers /: OpenSHMEM in the era of extreme heterogeneity : 5th Workshop, OpenSHMEM 2018, Baltimore, MD, USA, August 21-23, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available